1971
DOI: 10.1136/jnnp.34.6.682
|View full text |Cite
|
Sign up to set email alerts
|

Failure of vitamin B6 to reverse the L-dopa effect in patients on a dopa decarboxylase inhibitor

Abstract: SUMMARY Seven patients with Parkinsonism previously on L-dopa were placed on a regimen of L-dopa and alpha methyl dopa hydrazine (a dopa decarboxylase inhibitor). Two of these patients had previously shown marked clinical deterioration of the L-dopa improvement when given pyridoxine. None of the seven patients receiving alpha methyl dopa hydrazine demonstrated any change in their condition when given pyridoxine. The failure of vitamin B6 to reverse the clinical effect of L-dopa in patients receiving both L-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Lechat et al [13] first demonstrated in animals that previous administration of a peri pheral dopa decarboxylase inhibitor would block the ability of pyridoxine to antagonize the antiparkinson properties of L-dopa. Our studies [11], as well as those of Yahr et al [21] and Papavasiliou et al [17], have clear ly shown this to be the case also in parkinsonian patients simultaneously treated with L-dopa and a dopa decarboxylase inhibitor. None of the pa tients showed loss of L-dopa effect when given pyridoxine.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Lechat et al [13] first demonstrated in animals that previous administration of a peri pheral dopa decarboxylase inhibitor would block the ability of pyridoxine to antagonize the antiparkinson properties of L-dopa. Our studies [11], as well as those of Yahr et al [21] and Papavasiliou et al [17], have clear ly shown this to be the case also in parkinsonian patients simultaneously treated with L-dopa and a dopa decarboxylase inhibitor. None of the pa tients showed loss of L-dopa effect when given pyridoxine.…”
Section: Discussionsupporting
confidence: 51%
“…Paradoxically, they showed vi tamin B0 to cause a loss or reversal of the L-dopa effect [5,22]. Others have shown that vitamin B0 failed to reverse the clinical effect of L-dopa in patients receiving both L-dopa and a peripheral dopa decarboxylase in hibitor [11,17]. This suggests that B0-induced reversal of the L-dopa ef fect is due to accelerated decarboxylation of L-dopa to dopamine in extra cerebral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridoxine treatment has been demonstrated to reverse the clinical effect of l ‐dopa; however, when l ‐dopa was given in combination with a peripheral AADC inhibitor, such as carbidopa or benserazide, pyridoxine did not have this effect (Duvoisin et al. 1969; Klawans et al. 1971).…”
Section: Discussionmentioning
confidence: 99%
“…carbidopa, benserazide) with levodopa may minimize this interaction. [66] In a prospective, population-based, cohort study of 5289 people, higher dietary intake of vitamin B 6 was associated with a significantly lower risk of incident PD among smokers only; however, no reduction in risk was observed for dietary folate or vitamin B 12 . [44] The authors postulated that the limitation of the effect to smokers might have been due to a combined benefit of vitamin B 6 and smoking, which has been independently associated with a lower risk of PD (see section 2.5).…”
Section: Vitamins B 6 B 12 and Folatementioning
confidence: 97%